Atmospheric deposition fluxes of 137Cs associated with dust fallout in the northeastern Arabian Gulf. (December 2018) - Aba, A.; Al-Dousari, A.M.; Ismaeel, A.
Abstract: For many years, monitoring and determining the radioactivity of 137 Cs in the environment has considerable interest. This paper presents monitoring 137 Cs deposition fluxes during the period from 2009 to 2011. Dust fallout samples were collected from ten locations in Kuwait, and 137 Cs concentrations were determined using ultra low spectrometry system. The average of the annual atmospheric deposition fluxes of 137 Cs was 4.3, with an extreme value reaching 50 Bq m −2 . The monthly deposition rates of 137 Cs were attributed to seasonal increases in the spring. 137 Cs deposition fluxes showed a significant relationship with dust deposition and precipitation rates, where the correlation between the monthly dust fallout and the 137 Cs deposition fluxes and precipitation rates were approximately 0.95 and 0.81, respectively. The spatial monthly distribution of 137 Cs fluxes showed high rates in the southeastern part of Kuwait while the lowest rates were recorded along the coastlines. A strong correlation was observed between the annual 137 Cs and 40 K deposition rates considering that both radionuclides deposition were governed by similar conditions. It was concluded that long-range transport from the northwestern areas along with the effects from local dust washout and the site specify played a major role in controlling the rate of 137 Cs deposition. The estimated annual effective dose equivalent due to external and internal exposures was insignificant and can be ignored. It is worthwhile to continue investigating the source origin of 137 Cs in Kuwait to enhance understanding of the radiological hazards in the country. Highlights: Dust fallout samples were collected from ten locations in Kuwait; 137 Cs concentrations were determined using ultra low gamma spectrometry system. 137 Cs deposition fluxes were continuously observed and showed seasonally variations. The concentration of 137 Cs has been found to be enriched by long-range transport from its surroundings, mainly by the northwesterly dust sources. The radiological hazards associated with 137 Cs deposition in Kuwait are very small and can be ignored.